Preparation method of modified lithium manganese phosphate positive electrode material

By depositing lithium manganese phosphate particles in the carbon network structure of grapefruit peel, the problem of insufficient conductivity and lithium ion diffusion capacity of the positive electrode material of manganese phosphate is solved, and the material performance is improved and cost reduction is reduced, which is suitable for industrial production.

CN119176535APending Publication Date: 2024-12-24浙江格派钴业新材料有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411523488.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

The electronic conductivity and lithium ion diffusion ability of the lithium manganese phosphate cathode material are limited by its own structure, making it difficult to meet the needs of high-capacity lithium-ion batteries.

Method used

Grapefruit peels are used as biocarbon source, and lithium manganese phosphate particles are deposited in the biocarbon network structure through self-assembly process to form a modified composite material. Grapefruit peels are used as carbon framework to improve structural stability and conductivity and shorten lithium ions. and provide more Li+ adsorption sites.

Benefits of technology

It significantly improves the electrochemical performance of lithium manganese phosphate positive electrode material, improves the overall structural stability and conductivity, is suitable for large-scale industrial production, and reduces costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119176535A_ABST
    Figure CN119176535A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of preparation of lithium ion battery positive electrode materials, and discloses a preparation method of a modified lithium manganese phosphate positive electrode material, which comprises the following steps: (1) taking shaddock peel, cleaning with pure water, and drying in a drying oven to constant weight; (2) crushing the dried shaddock peel by using a crusher, then weighing shaddock peel powder and an activating agent according to a weight ratio, and dipping under a liquid phase condition; (3) drying the soaked shaddock peel powder in a drying oven, and then performing carbonization treatment under an anaerobic condition; (4) carrying out acid leaching treatment on the carbonized shaddock peel carbon, washing for multiple times, and drying; and (5) mixing the shaddock peel carbon with a raw material of lithium manganese phosphate and a solvent, drying, and carrying out heat treatment to obtain the positive electrode material. According to the prepared modified positive electrode material, the overall structural stability and conductivity of the material are effectively improved, the transmission path of Li < + > is shortened, and more Li < + > adsorption sites with capacitance behaviors are provided due to rich defects of the modified positive electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of lithium ion battery positive electrode materials, and specifically relates to a method for preparing a modified lithium manganese phosphate positive electrode material. Background Art

[0002] As a new type of energy storage device, lithium-ion batteries have been widely used in electric vehicles, mobile devices, computers and other fields due to their high energy density, good safety performance, good cycle stability, excellent rate performance and long service life.

[0003] The cathode material of lithium-ion batteries is a key factor affecting battery performance. The commercialized cathode material lithium iron phosphate is widely used due to its high theoretical capacity and good cycle stability, but it cannot meet the use requirements of high-capacity lithium-ion batteries due to its relatively low operating voltage. As a hot research topic for cathode materials today, olivine-type lithium manganese phosphate has the advantages of low cost, low toxicity, good cycle performance, stable structure, and high energy intensity. However, similar to lithium iron phosphate materials, lithium manganese phosphate materials are affected by their own structure, and their electronic conductivity and lithium ion diffusion capacity are severely limited.

[0004] Therefore, improving the electrochemical performance of lithium manganese phosphate, improving its synthesis method, and strengthening modification research are the research focuses in this field. To this end, scholars have comprehensively applied a variety of modification technologies, strengthened material design, and improved synthesis processes. Summary of the invention

[0005] In order to improve the electrochemical performance of lithium manganese phosphate, the present invention provides a modified lithium manganese phosphate positive electrode material and a preparation method thereof. The material uses grapefruit peel as a biological carbon source, and deposits lithium manganese phosphate particles on a biological carbon network structure through a self-assembly process to form a modified composite material. Grapefruit peel carbon is composited with lithium manganese phosphate positive electrode material, which not only serves as a carbon skeleton, but also improves the overall structural stability and conductivity of the material and shortens the Li + The rich defects also provide more Li with capacitive behavior. + Adsorption sites.

[0006] To achieve the above object, the present invention provides the following technical solutions: A method for preparing a modified lithium manganese phosphate positive electrode material comprises the following steps: (1) Take grapefruit peel, wash it with pure water, and dry it in an oven until constant weight; (2) crushing the grapefruit peel treated in step (1) with a pulverizer, then weighing grapefruit peel powder and an activator according to a mass ratio, and impregnating them under liquid phase conditions; (3) drying the grapefruit peel powder treated in step (2) in an oven, and then carbonizing the powder under anaerobic conditions to obtain grapefruit peel carbon; (4) acid leaching the grapefruit peel carbon, washing it several times and then drying it; (5) The grapefruit peel carbon treated in step (4) is mixed with raw materials of lithium manganese phosphate and solvent, dried and then heat-treated to obtain a modified lithium manganese phosphate positive electrode material coated with grapefruit peel carbon.

[0007] In the present invention, grapefruit peel is a biomass rich in cellulose and lignin, and is an ideal material for making porous carbon. Through the chemical activation method, the activator is infiltrated into the grapefruit peel. During the high-temperature pyrolysis and activation process, the erosion of the chemical substance on the precursor matrix is ​​enhanced, and the carbon is continuously decomposed and rearranged to form a carbon skeleton, thereby forming an amorphous graphite microcrystalline structure. After the pyrolysis is completed, the excess activator is washed and removed to form a pore structure in the carbon material.

[0008] In the present invention, grapefruit peel is selected as a biomass raw material, and the biomass carbon prepared after carbonization is used as a matrix to prepare a high-performance lithium manganese phosphate positive electrode material by compounding with lithium manganese phosphate. During the heat treatment process, lithium manganese phosphate crystal particles are formed and grown on the surface of the grapefruit peel carbon, and the growth process of the crystal particles is limited due to the influence of the grapefruit peel carbon pore size, which can significantly improve the overall conductivity of the carbon-coated positive electrode material. The raw materials are easy to obtain and are more suitable for large-scale industrial production.

[0009] In step (1), the pomelo peel is selected from the relatively soft and loose white flesh inside the pomelo peel.

[0010] The activator in step (2) is at least one of calcium chloride, potassium hydroxide, sodium hydroxide and sodium carbonate.

[0011] In step (2), the mass ratio of grapefruit peel powder to activator is 1:1-2.5. Loose and porous biomass carbon is obtained by adjusting the mass ratio of biomass raw material (grapefruit peel powder) to activator.

[0012] The concentration of the activator in step (2) is 1.0-3.0 mol / L, and the immersion time is 1-3 h.

[0013] In the step (3), when the carbonization treatment is carried out under anaerobic conditions, the carbonization temperature is 700-900° C. and the carbonization time is 2-5 hours.

[0014] In the present invention, if the reaction temperature is too high, the reaction speed may be too fast and cause the structure of the biomass carbon material to collapse; if the reaction temperature is too low, the reaction degree is not enough and no biomass carbon material with a loose structure can be obtained; if the reaction time is too long, excessive reaction may cause structural damage to the biomass carbon material; if the reaction time is too short, the reaction is insufficient and no biomass carbon material with a loose structure can be obtained.

[0015] In step (4), the acid leaching uses at least one of hydrochloric acid, sulfuric acid and nitric acid, and the acid concentration is 1-3 mol / L. During the acid leaching process, ultrasound assistance can be used to completely remove the residual activator and metal impurity elements.

[0016] In the step (5), the lithium manganese phosphate raw material includes a lithium source, a manganese source, a phosphorus source and a carbon source; the lithium source includes at least one of lithium carbonate, lithium hydroxide, lithium oxalate, lithium acetate, lithium phosphate and lithium dihydrogen phosphate; the manganese source includes at least one of manganese dioxide, manganese trioxide, manganese tetraoxide, manganese carbonate, manganese oxalate and manganese phosphate; the phosphorus source includes at least one of phosphoric acid, manganese phosphate, lithium dihydrogen phosphate, ammonium dihydrogen phosphate and diammonium hydrogen phosphate; the carbon source includes at least one of glucose, polyethylene glycol, starch, sucrose, fructose and polyvinyl alcohol.

[0017] In the step (5), the mass ratio of grapefruit peel carbon to the theoretical product of lithium manganese phosphate is x:1, where x=0.02-0.05.

[0018] In the step (5), the heat treatment is carried out under a protective atmosphere of high-purity nitrogen or high-purity argon, the heat treatment temperature is 650-750°C, and the heat treatment time is 6-10h.

[0019] Compared with the prior art, the present invention provides a method for preparing a modified lithium manganese phosphate positive electrode material. By using cheap grapefruit peel as a biomass carbon source and compounding it with a lithium manganese phosphate positive electrode material as a biomass carbon material with a skeleton structure, the overall structural stability and electrical conductivity of the material are improved. The method has the advantages of simple operation, low equipment requirements, low cost, and is conducive to large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is the SEM image of the grapefruit peel carbon prepared in Example 1; Figure 2 This is the XRD pattern of the modified lithium manganese phosphate positive electrode material prepared in Example 1. DETAILED DESCRIPTION

[0021] The technical solutions in the embodiments of the present invention will be described in detail below in conjunction with the accompanying drawings in the embodiments of the present invention. Example

[0022] (1) Take the white part of the grapefruit peel, wash it with pure water, and dry it in an oven at 110°C until constant weight.

[0023] (2) The dried grapefruit peel was crushed with a pulverizer, and grapefruit peel powder and calcium chloride were weighed in a mass ratio of 1:2. The calcium chloride was prepared into a 2 mol / L solution, and the grapefruit peel powder was immersed in the calcium chloride solution for 2.5 h.

[0024] (3) Dry the above solution in an oven at 110°C, cool it, place it in a tube furnace and introduce high-purity nitrogen. The temperature was raised to 750°C at a heating rate of 5°C / min and then calcined for 3 h. After cooling to room temperature, the sample was taken out.

[0025] The sample was ground and dissolved in 2 mol / L dilute hydrochloric acid for ultrasonic cleaning. Finally, the sample was washed with deionized water until it was neutral to remove residual impurity elements. After drying at 110° C., grapefruit peel carbon powder was obtained.

[0026] Lithium carbonate, manganese carbonate and diammonium phosphate were weighed according to a stoichiometric ratio of 0.5:1:1 and put into a ball mill, 15% glucose and 3% grapefruit peel carbon of the theoretical lithium manganese phosphate product were added, and an appropriate amount of anhydrous ethanol was added as a dispersant. The slurry was taken out at a speed of 400 rpm and placed in a drying oven for drying at 110°C. The dried mixture was sintered in a nitrogen atmosphere, the temperature was increased to 710°C at a rate of 5°C / min and sintered for 8 hours, and then cooled to room temperature to obtain a lithium manganese phosphate positive electrode material modified by grapefruit peel carbon. Example

[0027] The difference from Example 1 is that in step (5), the amount of grapefruit peel carbon added is adjusted from 3% to 5%, and the rest is the same as Example 1. Example

[0028] The difference from Example 1 is that in step (2), grapefruit peel powder and calcium chloride are weighed according to a mass ratio of 1:2.5, and the rest is the same as Example 1. Example

[0029] The difference from Example 1 is that in step (2), the calcium chloride activator is replaced by a sodium hydroxide activator, and the rest is the same as Example 1. Example

[0030] The difference from Example 1 is that in step (3), the carbonization temperature is adjusted to 900° C., and the rest is the same as Example 1.

[0031] Comparative Example The difference from Example 1 is that grapefruit peel carbon is not added.

[0032] Lithium carbonate, manganese carbonate and ammonium dihydrogen phosphate were weighed according to a stoichiometric ratio of 0.5:1:1 and placed in a ball mill, 15% glucose of the theoretical lithium manganese phosphate product was added, and an appropriate amount of anhydrous ethanol was added as a dispersant. The slurry was taken out at a speed of 400 rpm for 4 hours, and placed in a drying oven for drying at 110°C. The dried mixture was sintered in a nitrogen atmosphere, raised to 710°C at a rate of 5°C / min, sintered for 4 hours, and then cooled to room temperature to obtain a lithium manganese phosphate positive electrode material without grapefruit peel carbon modification.

[0033] The active material was mixed with the conductive agent and the binder (80:10:10) in NMP solvent according to the established mass ratio, and then coated on the aluminum foil current collector after stirring evenly, and dried in a vacuum drying oven at 120°C for 12 h. When the drying oven temperature dropped below 60°C, the battery pole piece was taken out and a circular battery pole piece with a radius of 7 mm was cut out. The pole pieces were assembled into R2016 button cells in a glove box with a high-purity Ar atmosphere. The assembled button cells were kept at a constant temperature of 25°C for 12 h and then various electrochemical performance tests were performed.

[0034] The test results are shown in Table 1 below.

[0035] Table 1 Performance test results No. 0.1C discharge capacity mAh / g First effect% 1C discharge capacity mAh / g 1C cycle 100 cycles capacity retention rate% Example 1 140.5 91.5 131.7 88.7 Example 2 138.7 90.8 129.5 89.3 Example 3 140.2 91.2 130.6 88.4 Example 4 141.3 91.7 131.3 87.9 Example 5 139.6 90.7 129.6 87.3 Comparative Example 1 128.5 85.5 101.5 76.8 Figure 1 This is the SEM image of grapefruit peel carbon. From the image, we can see that the surface of the sample is uneven, with obvious pits, defects and pores. This structure can provide more active sites for the embedding of lithium ions, thereby promoting the diffusion and transfer of lithium ions, which is beneficial to improving the electrochemical performance.

[0036] Figure 2 The XRD spectrum of the modified lithium manganese phosphate positive electrode material prepared in Example 1, all diffraction peaks correspond to the diffraction peaks of the lithium manganese phosphate standard card, and no other obvious impurity peaks are seen, indicating that the prepared material has high purity and crystallinity. No diffraction peaks of carbon are seen in the XRD spectrum, indicating that carbon exists in an amorphous form.

[0037] By comparing the examples in Table 1 with the comparative examples, it can be seen that the electrical properties of the modified lithium manganese phosphate positive electrode material doped with grapefruit peel carbon are significantly improved. This is because, in the present application, grapefruit peel is used as a biomass carbon source to deposit lithium manganese phosphate particles on the biocarbon network structure through a self-assembly process, which not only improves the overall structural stability and conductivity of the material, but also shortens the Li + The rich defects also provide more Li with capacitive behavior. + Adsorption sites.

[0038] The above content describes the technical principles, beneficial effects and features of the present invention. It should be pointed out that the above is only a preferred implementation mode of the present invention, but is not limited to the above embodiments. For technicians in the technical field to which the present invention belongs, some improvements and optimizations can be made without departing from the content of the present invention, which should be regarded as belonging to the protection scope of the present invention.

Claims

1. A method for preparing a modified lithium manganese phosphate positive electrode material, characterized in that: The following steps are involved: (1) Take grapefruit peel, wash it with pure water, and dry it in an oven until constant weight; (2) crushing the grapefruit peel treated in step (1) with a pulverizer, then weighing grapefruit peel powder and an activator according to a mass ratio, and impregnating them under liquid phase conditions; (3) drying the grapefruit peel powder treated in step (2) in an oven, and then carbonizing the powder under anaerobic conditions to obtain grapefruit peel carbon; (4) acid leaching the grapefruit peel carbon, washing it several times and then drying it; (5) The grapefruit peel carbon treated in step (4) is mixed with raw materials of lithium manganese phosphate and solvent, dried and then heat-treated to obtain a modified lithium manganese phosphate positive electrode material coated with grapefruit peel carbon.

2. The method for preparing a modified lithium manganese phosphate positive electrode material according to claim 1, characterized in that: In step (1), the pomelo peel is selected from the relatively soft and loose white flesh inside the pomelo peel.

3. The method for preparing a modified lithium manganese phosphate positive electrode material according to claim 1, characterized in that: The activator in step (2) is at least one of calcium chloride, potassium hydroxide, sodium hydroxide and sodium carbonate.

4. The method for preparing a modified lithium manganese phosphate positive electrode material according to claim 1, characterized in that: In the step (2), the mass ratio of the grapefruit peel powder to the activator is 1:1-2.

5.

5. The method for preparing a modified lithium manganese phosphate positive electrode material according to claim 1, characterized in that: The concentration of the activator in step (2) is 1.0-3.0 mol / L, and the immersion time is 1-3 h.

6. The method for preparing a modified lithium manganese phosphate positive electrode material according to claim 1, characterized in that: In the step (3), when the carbonization treatment is carried out under anaerobic conditions, the carbonization temperature is 700-900° C. and the carbonization time is 2-5 hours.

7. The method for preparing a modified lithium manganese phosphate positive electrode material according to claim 1, characterized in that: In the step (4), the acid leaching uses at least one of hydrochloric acid, sulfuric acid and nitric acid, and the acid concentration is 1-3 mol / L.

8. The method for preparing a modified lithium manganese phosphate positive electrode material according to claim 1, characterized in that: In the step (5), the lithium manganese phosphate raw material includes a lithium source, a manganese source, a phosphorus source and a carbon source; the lithium source includes at least one of lithium carbonate, lithium hydroxide, lithium oxalate, lithium acetate, lithium phosphate and lithium dihydrogen phosphate; the manganese source includes at least one of manganese dioxide, manganese trioxide, manganese tetraoxide, manganese carbonate, manganese oxalate and manganese phosphate; the phosphorus source includes at least one of phosphoric acid, manganese phosphate, lithium dihydrogen phosphate, ammonium dihydrogen phosphate and diammonium hydrogen phosphate; the carbon source includes at least one of glucose, polyethylene glycol, starch, sucrose, fructose and polyvinyl alcohol.

9. The method for preparing a modified lithium manganese phosphate positive electrode material according to claim 1, characterized in that: In the step (5), the mass ratio of grapefruit peel carbon to the theoretical product of lithium manganese phosphate is x:1, where x=0.02-0.

05.

10. The method for preparing a modified lithium manganese phosphate positive electrode material according to claim 1, characterized in that: In the step (5), the heat treatment is carried out under a protective atmosphere of high-purity nitrogen or high-purity argon, the heat treatment temperature is 650-750°C, and the heat treatment time is 6-10h.